Plant genetic resources education in Malaysia: ways forward: Report from a one-day consultation, 1 July 2011 - Rudebjer, P.G.; Bioversity International (2011)
A consultation in 2009 on advancing higher education on plant genetic resources (PGR) in the Asia, Pacific and Oceania region resulted in the ‘Tsukuba Action Plan’, covering course enhancement, degree enhancement, short courses, networking, and awareness. Eighteen months on, Bioversity International and Malaysian universities organized a one-day workshop on 1 July 2011 to review Malaysia’s progress in implementing the Action Plan. This report gives an update on agrobiodiversity education activities in the country since 2009, informs on existing networks, platforms and other resources that can support such education, and recommends further steps towards strengthening PGR and agrobiodiversity education in Malaysia.